Understanding the caring network of podoconiosis patients in Rwanda: a qualitative study - Risat, Md Ilias Kamal; Davey, Gail; Mugume, Peter; Zaman, Shahaduz (Frontiers in Tropical Diseases, 2024)
Introduction Globally, a total of almost 4 million people live with podoconiosis in 32 potentially endemic countries including Rwanda. Podoconiosis is a non-infectious geochemical disease that causes massive swelling of the lower leg and is caused by long-term exposure to red clay soil found in tropical highland areas. The disease is a disabling neglected tropical disease (NTD) and is associated with profound stigma, discrimination and comorbid mental health conditions. Treatment interventions are commonly known as morbidity management and disability prevention. Both biomedical and traditional treatments are used by affected people. However, understandings informed by the social sciences of care in the context of NTDs are largely unexplored. This study explored the perspectives and experiences of care among care receivers (podoconiosis patients) and caregivers (family members, traditional healers) in the district of Huye, Rwanda. Method The study used qualitative methods including seventeen InDepth Interviews (eleven patients, two traditional healers, two care professionals, and two family members) and participant observation in a health centre and patients’ houses. Result A caring network was found amongst the podoconiosis patients, their family members, care professionals and traditional healers. Caring network is not only about the medical treatments, but also about the caring relationship amongst them. Discussion Using notions of ‘Network’ and ‘Collectives’, from the care ethics literature the study shows that in addition to care work requiring professional know-how, it is also about the relationships between patients, their families, traditional healers, and biomedical care professionals.